Prognostic value of homocysteine and highly sensitive cardiac troponin T in children with acute heart failure - Doaa El-Amrousy (Journal of the Saudi Heart Association, 2018)
Objective: Heart failure (HF) is a progressive disorder in children. Many HF biomarkers have been identified to assess its severity and predict its course. The aim of this study was to evaluate the prognostic value of plasma levels of homocysteine (HCY) and highly sensitive cardiac troponin T (hs-cTnT) in children with HF. Materials and Methods: Eighty children with acute HF were enrolled in this study as the patient group and 80 healthy children of matched age and sex served as the control group. HCY and hs-cTnT serum levels were measured before and after HF treatment; additionally, echocardiographic examinations were performed before and after therapy. All patients were followed up for 3 months. Results: Plasma levels of HCY and hs-cTnT were significantly higher in children with HF before treatment, compared with their levels in children with HF after treatment and with the control group. This increase in serum levels of both biomarkers was associated with increased severity of HF according to the Ross classification of HF. HCY had higher specificity, positive predictive value, and accuracy than hs-cTnT. Serum levels of both biomarkers had a significant positive correlation with cardiomegaly and a significant negative correlation with left ventricular ejection fraction and fraction shortening. Marked elevation of both serum biomarkers was significantly associated with poor outcome with mortality rate of 10%. Conclusion: Plasma HCY and serum hs-cTnT levels have a good prognostic value in children with congestive heart failure (CHF) and their levels significantly correlated with clinical and echocardiographic data, severity of HF, and adverse outcome in children with CHF. Keywords: Acute heart failure, Children, Highly sensitive cardiac troponin T, Homocysteine, Prognostic